One-Year Outcomes Using Ranibizumab for Neovascular Age-Related Macular Degeneration: Results of a Prospective and Retrospective Observational Multicentre Study - Lars Hjelmqvist; Charlotte Lindberg; Pär Kanulf; Henrik Dahlgren; Ingrid Johansson; Annica Siewert (Journal of Ophthalmology)
The Swedish Lucentis Quality Registry is a 12-month, open-label, observational, prospective, and retrospective study of ranibizumab administration for wet AMD. Visual acuity (VA) was measured with Snellen or ETDRS chart in 370 patients (66.8% women; age range 46–93 years). In total, a mean of 4.7±1.6 injections per patient (range 1–10) was given to month 12. Mean VA score was 58.3±12.2 letters before treatment, 63.3±12.5 after 3 injections (Δ4.9±10.1 letters from baseline), and 59.3±16.2 at 12 months (Δ1.0±13.6). VA score from baseline to month 12 was stable in 74.4% of patients, improved by 15 letters/3 lines or more in 14.7%, and decreased by ≥15 letters/3 lines in 10.9% of patients. With a mean of 4.7 ranibizumab injections per patient per year, mean VA was stabilised but not increased. To maintain the initial gain seen after the first three injections, an average of 1.8±1.5 additional injections does not appear to be adequate.